1991
DOI: 10.1038/sj.bdj.4807484
|View full text |Cite
|
Sign up to set email alerts
|

Reattachment of a fractured central incisor tooth fragment

Abstract: While the introduction of the acid-etch technique with composite materials has revolutionised the restoration of fractured incisor teeth, it is possible that restoration of such teeth using the fractured fragment may produce a superior result. The technique, with possible advantages and disadvantages, is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
7

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 0 publications
0
48
0
7
Order By: Relevance
“…This case report outlines the management of one such case using previously accepted techniques [2][3][4][5][6][7][8][9]13 and introducing a means of relocating and positioning tooth tissue fragments during reattachment .…”
Section: Practicementioning
confidence: 99%
“…This case report outlines the management of one such case using previously accepted techniques [2][3][4][5][6][7][8][9]13 and introducing a means of relocating and positioning tooth tissue fragments during reattachment .…”
Section: Practicementioning
confidence: 99%
“…In the first two cases, gross exposures of the pulp during the traumatic incident made root canal therapy necessary, but in the last case report a small exposure was treated using the bonding/luting system. 35,49,50 advantage. 22 As an additional study finding when reviewing cases of fragment reattachment, these authors reported that 50% of the reattached fragments were lost within the first year when only enamel bonding was used, while 3 years elapsed before 50% of fragments were lost when dentine bonding was carried out.…”
Section: Case Reportsmentioning
confidence: 99%
“…35,49,50 Report 1 describes the use of dentine and enamel bonding to effect a repair, and Reports 2 and 3 describe the use of an adhesive luting system. In the first two cases, gross exposures of the pulp during the traumatic incident made root canal therapy necessary, but in the last case report a small exposure was treated using the bonding/luting system.…”
Section: Case Reportsmentioning
confidence: 99%
“…Chosak and Eidelman (65) have developed the concept of reattachment for fractured incisors using the patient's natural crown, and this should be the first choice for restoration of fractured teeth if a usable fragment is available (66)(67)(68). Various techniques for reattachment include the use of an enamel/circumferential bevel beforehand (69,70), placement of a chamfer at the fracture line after bonding (71,72), use of a V-shaped enamel notch (7,73), placement of an internal groove (74,75) or a superficial overcontour over the fracture line (75), or simple attachment with no additional preparation (76). The use of a variety of materials as bonding agents is advocated (77)(78)(79)(80).…”
Section: Discussion and Treatment Optionsmentioning
confidence: 99%
“…The use of a variety of materials as bonding agents is advocated (77)(78)(79)(80). Hydrophilic adhesive agents with light cured/dual cured resin cement (12), bonding agents with flowable resins, hybrid or microfilled resin composites (7,69,(81)(82)(83), dentine adhesives with or without unfilled resins (84), dual or self-cured luting cements (75), light-cured luting cement (85), and self-etch adhesives with microhybrid composites (66) have been used with varying results (76). Developments in adhesive dentistry have improved the outcome by facilitating ultraconservative preparation techniques, and allowing "biologic restoration" (12), thus improving the esthetic outcome by retaining natural translucency and surface texture and reducing cost and chair time while increasing patient acceptance (12,66,76,86,87).…”
Section: Discussion and Treatment Optionsmentioning
confidence: 99%